Bending Strength Analysis of Composite Materials with Coconut Fiber Reinforcement Using Manual Hand Lay-Up Method - asrul, asrullah; Setiawan, M. Yasep; Maksum, Hasan; Hidayat, Nuzul; Susanto, Edy; Nasution, Ichsan (Universitas Negeri Padang, 2025)
This study investigates the mechanical performance of coconut coir fiber-reinforced composites with volume fractions of 30% and 40%, fabricated using the Manual Hand Lay-Up method. Specimens were tested under three-point bending following ASTM D790-03 to evaluate flexural strength. Results show that composites with a 30% fiber volume exhibit superior bending strength and stiffness compared to those with 40%, indicating a more optimal fiber–matrix ratio. The reduction in performance at higher fiber content is attributed to uneven resin distribution and inadequate fiber impregnation. These findings highlight the potential of coconut coir as a sustainable reinforcement material and emphasize the importance of optimizing fiber volume and manufacturing methods. The study recommends the use of alternative fabrication techniques, such as vacuum infusion, to improve resin homogeneity and mechanical reliability, particularly for structural and lightweight composite applications.